Effect of ethrel on phenolic changes during ripening of off-season fruits of mango (Mangifera indica L. var. Neelum) - C. Tamilmani, T. Venkatesan and (Current Botany, 2011)
The present investigation is aimed at studying the effect of ethrel on the ripening of offÃ¢â‚¬â€œseason fruits of Mangifera indica L. var. Neelum. The control fruits were kept in the laboratory naturally while the experimental fruits were treated with different concentrations of ethrel (100, 200 and 300ppm). In control fruits, partial ripening led to incomplete metabolic changes, which did not alter the presence of sourness in the fruits. Hence, they were not fit to be eaten.Ã‚Â On the other hand, the fruits treated with different concentrations (100, 200 and 300ppm) of ethrel ripened on 13th day, 11th day and 9th day respectively after treatment. The colour changed from green greenish to yellow and the fruits were palatable in nature. The colour changed from green to greenish yellow to yellow. On the other hand, in the control fruits, partial ripening led to incomplete metabolic changes, which did not alter the presence of sourness in the fruits, and hence, they were not fit to be eaten.Ã‚Â All the studies were carried out using the peel and the pulp of fruit tissues individually and the following results were obtained during the process of ripening. The phenols decreased during ripening, both in the treated and control fruits. On the other hand, the activity of peroxidase, polyphenoloxidase and catalase increased. Among the different 100, 200 and 300 ppm ethrel treatments, the 200 ppm alone had the optimum effect on the ripening of offÃ¢â‚¬â€œseason fruits of mangifera indica L. var. Neelum.